Patryk89046viz Patryk89046viz Matematyka Rozwiązane Usuń nawiasy i wykonaj redukcję wyrazów podobnych: a. (2x – 1) + (3x – 2) – (4x – 6) = b. ( – y + 4) – (2y – 1) + (3y + 3) = c. 2x – 5 – (x – 3) = d. 2y + 6 + (3y + 5) = e. (3x – 6) – (–2x + 4)= f. – (–2y – 5) + (–3y +3) = g. 5(–x – 8) + 6 (7 – 3x) = h. 2(8x + 3y) – 8(–5 + 2x) – 11y = i. 3(a + b) – 6(a – b) – 5(2a – 4b) = j. (8x – y) – (3x +y) – (–5x -2y+7) = k. 8[2x – (4y – 3x)] – 8[3x – (2x + 9y)] = l. –[2x – (9,5x + 0,26)] – [3,5x + (0,18x – 1,6)] = Pls na dziś potrzebuje